2009
DOI: 10.3168/jds.2008-1356
|View full text |Cite
|
Sign up to set email alerts
|

Differences in udder health and immune response traits of Holstein-Friesians, Norwegian Reds, and their crosses in second lactation

Abstract: The objective of this study was to investigate potential differences in udder health and immune response traits among Holstein-Friesian (HF), Norwegian Red (NR), and NR x HF (NRX) cows on 30 commercial Irish dairy farms. A total of 648 second-lactation cows (HF n = 274, NR n = 207, and NRX n = 167) were immunized with hen egg white lysozyme (HEWL) to induce antibody-mediated immune response (AMIR). Candida albicans was used to induce a cell-mediated immune response, with in vivo delayed-type hypersensitivity u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
1
20
1
1
Order By: Relevance
“…Similar findings have been recorded in other studies, with Walsh et al (2007) observing NR cows to have a lower SCS than HF cows in a 5-yr study. Similarly, Begley et al (2008) observed NR cows to have a significantly lower SCS than Holstein cows during their first lactation in a study conducted on 46 Irish farms and, in a further analysis of data from the same study (30 farms), Begley et al (2009) found average SCC and peak SCC to be lower with NR cows during their second lactation. Although SCC is known to be positively genetically correlated with milk yield (Mrode and Swanson, 1996), only relatively small differences existed in milk yields between breeds in the current study, suggesting that the lower SCC observed with the NR cows was largely a function of the selection program that has been implemented in Norway.…”
Section: Udder Healthmentioning
confidence: 83%
See 1 more Smart Citation
“…Similar findings have been recorded in other studies, with Walsh et al (2007) observing NR cows to have a lower SCS than HF cows in a 5-yr study. Similarly, Begley et al (2008) observed NR cows to have a significantly lower SCS than Holstein cows during their first lactation in a study conducted on 46 Irish farms and, in a further analysis of data from the same study (30 farms), Begley et al (2009) found average SCC and peak SCC to be lower with NR cows during their second lactation. Although SCC is known to be positively genetically correlated with milk yield (Mrode and Swanson, 1996), only relatively small differences existed in milk yields between breeds in the current study, suggesting that the lower SCC observed with the NR cows was largely a function of the selection program that has been implemented in Norway.…”
Section: Udder Healthmentioning
confidence: 83%
“…Indeed, in this latter study, evidence existed of increased culling due to poor udder health with the HF breed, in agreement with the findings of the current study. Begley et al (2009) also observed an increased primary antibody-mediated immune response with NR compared with HF cows, and suggested that this might be indicative of a greater ability to combat initial infection or challenge, especially in relation to extracellular pathogens. However, those authors observed no difference in cell-mediated immune response between breeds, and noted that associations between SCS or mastitis occurrence and immune responses were inconsistent.…”
Section: Udder Healthmentioning
confidence: 84%
“…Dairy MIS is a recorder-based computerised database where detailed information regarding stock, farm inputs and production events are recorded on a regular basis. These heifers were part of a breed comparison study, detail of which is available from Begley et al (2009) and Archbold et al (2011). Herds were visited once, on average 9 (s.d.…”
Section: Methodsmentioning
confidence: 99%
“…On the Dutch organic farms, HF cows are, based on milk and protein yields (in kg produced in 305 days), superior to all of the other breeds. HF cows are also shown to be superior for milk and protein yields on conventional farms in Ireland (Begley et al, 2009;Penasa et al, 2010) and in United States of America (Heins et al, 2008). When analysing the fat production (in kg or as percentage of the milk contents), Jersey cows showed highest production levels on Dutch organic farms.…”
Section: Milk Production Traitsmentioning
confidence: 99%